Comparison of Radiographic Images in Shoulder Joint Examination in AP Projection With AP Axial Rays Angle Variations of 20°, 30° and 40° Caudo Cranially - Arifin, Nur; Arif, Muhammad; Casidi (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Background: The shoulder joint examination technique is an imaging method using X-rays to visualize the anatomical structures of the shoulder joint accurately. Different beam angles in axial (AP) projections can affect the clarity and diagnostic quality of the resulting images. Purpose: The purpose of this scientific paper is to determine the technique for examining the shoulder joint using axial (AP) projections with variations in beam angles of 0°, 20°, 30°, and 40°, and to identify which angle produces the most optimal image. Method: This study used a descriptive method. The examination was conducted by applying different projection angles and assessing the resulting images for clarity and anatomical detail. The average scores were recorded for each angle. Results: The projections obtained an average score of 3.03 for the 0° angle, 2.93 for the 20° angle, 3.21 for the 30° angle, and 2.93 for the 40° angle. Based on the analysis, the 30° angle was concluded to be the most optimal projection, achieving the highest average score of 3.21, and can be considered the best angle for shoulder joint examination in this study.